Hydrogen Transfer Reaction to Imines with 2-Propanol Catalyzed by Ruthenium (Ii) Complexes Containing Nitrogen-Phosphorus (Npn) Ligands. Experimental and Computational Studies - Moya-Duran, S; Moya-Duran, S; Negrete-Vergara, C; Negrete-Vergara, C (Elsevier B.V., 2024)
This work reports the synthesis and characterization of ruthenium(II) complexes containing nitrogen-phosphorus-nitrogen (NPN) ligands, with L1 = N-(phenyl(pyridin-2-ylamino)phosphino)pyridin-2-amine and L2 = 4-methyl-N-((4-methylpyridin-2-ylamino)(phenyl)phosphino)pyridin-2-amine. The ruthenium complexes RuCl2PPh3(L1) (1) and RuCl2PPh3(L2) (2) show high activities in catalytic transfer hydrogenation of different substituted benzylideneanilines, with turnover frequencies up to 5882 h−1 and 5294 h−1, respectively. The RuCl(CO)PPh3(L1) (3) and RuCl(CO)PPh3(L2) (4) complexes were non-active in the reaction studied. Theoretical calculations conducted for complex 4 showed that the carbonyl group promotes σ-orbital interactions and backdonation phenomena from the metal centre to the π* orbitals in the CO ligand, presenting a strong orbital contribution. This supports the hypothesis that complexes 3 and 4 are less reactive species and therefore present poor or null catalytic performance in the reaction studied. © 2024